Palladium-catalyzed synthesis of alkynylated 1,4: 5,8:11,14:15,18-tetrasulfido(20)annulenes - Dahlmann, Uwe; Krieger, Claus; Neidlein, Richard (European journal of organic chemistry, 1998)
The syntheses of tetraalkynylated tetrasulfido[20]annulenes 2a−d are described. Treatment of the corresponding brominated tetrasulfido[20]annulene 5a (easily available by McMurry coupling of the brominated 2,2′-bithiophene-5,5′-dicarbaldehydes, 3a) with various acetylenes in the presence of Pd(II) and Cu(I) in NH(iPr)2 yields acetylenic tetrasulfido[20]annulenes 2a−d.
Gesehen am 06.07.2023
Die Zahl "20" im Zusatz zum Titel wird in eckigen Klammern dargestellt